Análisis económico del cultivo de banano orgánico (Musa paradisiaca) en el Grupo Hoyos S.A- cantón Quinsaloma.” - Mena Vélez, Kevin Yandry (2019)
Banana activity in Ecuador for sixty years has had and has an important weight in the development of the country, both economically and socially, in order to show the advantages of the production and consumption of safe organic food , this is free of chemicals, which are now demanding international markets, making it attractive to devote part of banana production to an organic system, reducing areas of conventional cultivation, this research project aims to: analyze the production costs of the cultivation of organic banana from flowering to harvest in the Hoyos SA-Cantón Quinsaloma group. of the research methodology, the types of Analytical and Deductive research were used, and as sources of information, interviews with experts and direct observation were used. From the analysis and interpretation of the results it was concluded: The total costs incurred in the estates fluctuate between 520.60 dollars for one hectare in Solo Banana and 543.02 dollars for Maravilla Media, the latter 3.7% more than Santa Lucia and 4, 2% on Banana Only. The highest economic income was obtained in the Santa Lucia farm; while the highest costs were recorded in the Hacienda Maravilla Media. The profitability in the production of organic bananas among the farms of the Hoyos S.A group fluctuates between 8% and 29%, with the Santa Lucia farm having the highest value. Keywords: Fertilization, profitability, benefits, organic, flowering, harvest.